Knowledge, attitude and perception of Halal and Haram ingredients in medicines among pharmacists and pharmacy assistants in Hospital Universiti Sains Malaysia - Sukeri, Ahmad Khairul Azwar; Azuddin, Aznie; Othman, Emmy Insyirah (2016)
This study was conducted as a cross-sectional study which is carried out between June 2015 and March 2016. Structured and self-administered questionnaires are used to evaluate Knowledge, Attitude and Perception (KAP) of Halal and Haram ingredients in medicines, among pharmacists and pharmacy assistants in Hospital UniversitiSains Malaysia, KubangKerian, Kelantan. The research was done at HopitalUniversitiSains Malaysia (HUSM), KubangKerian, Kelantan. The study was conducted on a target sample of 35 pharmacists and 68 pharmacy assistants which are the total number of pharmacists and pharmacy assistants in this hospital during the study is conducted. Therefore, there is no exclusion in this study. However, under unwanted circumstances, a few respondents cannot take part in this study. Study settings include Outpatient Pharmacy Unit, Inpatient Pharmacy Unit, Aseptic Dispensing Unit, Radiopharmaceutical Unit, Therapeutic Drug Monitoring Unit, Pharmaceutical Manufacturing Unit, Store Management Unit, Drug Information Unit, Clinical Pharmacy Unit, and Administration and Finance Unit. The questionnaires are distributed directly to the respondents. From the questionnaires swe manage to collect, we go through all of it and key in the data into Microsoft Excel software to get the result in a table form. Instead, this result will be known and soon it is beneficial for future research indeed. Thus, the hospital might achieve their real objectives to evaluate Knowledge, Attitude and Perception (KAP) of Halal and Haram ingredients in medicines, among pharmacists and pharmacy assistants.